Incidence of MIS-C and the Comorbidity Scores in Pediatric COVID-19 Cases - KARAHASAN, AYŞEGÜL; KEPENEKLİ KADAYİFCİ, EDA (My University, 2021)
BACKGROUND: We aimed to determine the incidence of multisystem ınflammatory syndrome in children (MIS-C) in pediatric coronavirus disease 2019 (COVID-19) cases and to define the relationships between the need for hospitalization, the development of MIS-C, and Charlson (CCI) and Pediatric comorbidity index (PCI) scores. METHODS: All pediatric COVID-19 cases between March 25, 2020, and December 28, 2020, in the Marmara University Pendik Training and Research Hospital were enrolled. Patients who needed hospitalization were determined. Hospital records were reexamined to identify those diagnosed as having MIS-C. CCI and PCI were used to validate the comorbidity status. RESULTS: Among 2055 pediatric COVID-19 cases, 1340 were included in the study. Two hundred thirteen patients (15.9%) had at least one comorbidity. All the patients or their parents were interviewed about the need for hospitalization, except for the acute period. Six patients had MIS-C, which corresponds to a MIS-C incidence of 0.4%. The need for hospitalization increased in the patients with comorbidities (p<0.05). No correlation was found between the comorbidity scores and the development of MIS-C. The need for hospitalization increased in the patients with CCI scores of ≥2 and PCI scores of ≥4 (p<0.05). CONCLUSIONS: Our study is the first to examine the incidence of MIS-C, which was 0.4%, by long-term follow-up of pediatric COVID-19 cases and to demonstrate that the CCI and PCI can be used to predict the need for hospitalization and prognosis of pediatric patients with COVID-19.
Keywords: COVID-19; Comorbidity; Incidence; Hospitalization; MIS-C